The Potential of Algae in Treating Celiac Disease - Asri, Nastaran; Rostami-Nejad, Mohammad; Zamanian Azodi, Mona; Rezaei, Mitra; Robati, Reza M (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Compounds found in algae, such as bioactive substances, sulfated polysaccharides, and polyunsaturated fatty acids, have been found to have positive effects on the immune system. Previous research has shown that algae can also benefit digestive system disorders. They possess antioxidant and anti-inflammatory properties and can influence the balance of gut microbiota and maintain the integrity of the intestinal lining. Celiac disease (CD), a disorder caused by an abnormal immune response to gluten, results in inflammation and damage to the intestinal lining, leading to problems with nutrient absorption. Although a lifelong gluten-free diet is the only treatment option for this disease, it is challenging to adhere to. Therefore, recent studies have focused on finding supplementary or alternative therapies for celiac disease patients. Traditional medical treatments, like anti-inflammatory and biological drugs, are associated with significant side effects and are not suitable for supplementary therapy for this group of patients. Algae shows promise as a potential research area for treating CD; however, their specific effects on this condition have not been widely studied. The aim of this study was to gather current information and draw attention to the potential use of algae extracts in treating CD to encourage further research in this field.